Preparation and application of binary acid-base CaO-La2O3 catalyst for biodiesel production - Lee, H. V.; Juan, J. C.; Yap, Taufiq Yun Hin (Elsevier, 2015)
A simple method was developed for biodiesel production from non-edible Jatropha oil which contains high free fatty acid using a bifunctional acid-base catalyst. The acid-base catalyst comprising CaO and La2O3 mixed metal oxides with various Ca/La atomic ratios were synthesized via co-precipitation method. The effects of Ca/La compositions on the surface area, acidity-basicity and transesterfication activity were investigated. Integrated metal-metal oxide between Ca and La enhanced the catalytic activity due to well dispersion of CaO on composite surface and thus, increased the surface acidic and basic sites as compared to that of bulk CaO and La2O3 metal oxide. Furthermore, the transesterification reactions resulted that the catalytic activity of CaOeLa2O3 series were increased with Ca/La atomic ratio to 8.0, but the stability of binary system decreased by highly saturated of CaO on the catalyst surface at Ca/La atomic ratio of 10.0. The highest biodiesel yield (98.76%) was achieved under transesterification condition of 160C, 3h, 25 methanol/oil molar ratio and 3 wt.%. In addition, the stability of CaO-La2O3 binary system was studied. In this study, Ca-La binary system is stable even after four cycles with negligible leaching of Ca2þion in the reaction medium.